ANALYZING DEIXIS IN A NARRATIVE TEXT ENTITLED “AN ICY MONSTER STORY” - Desti Apriliani Rahmah; Setya Resmini (IKIP Siliwangi, 2021)
Deixis is the study of how to analyze or understand a word related to the person, place and time in a sentence. This study aims to find out the total and categories of deixis in a narrative text entitled